(untitled) (Fiep Bulletin - online, 2016)
Introduction: The cancer cases has increased significantly worldwide, mostly from the last century, and is today one of the most important public health problems worldwide. As a profession in the health, physical education professional in Brazil seems often not present in their curricular or complementary disciplines that address activities explore or produce knowledge on the subject. Objectives: This study aims to evaluate and score the knowledge of university physical education students about cancer, its risk factors and their relationship with a sedentary lifestyle. Materials and Methods: This is a study of epidemiologic, cross-sectional, population-based, where 217 students participated voluntarily aged between 17 and 29, originating from two IES is an established in the Midwest Region of Minas Gerais and other in the northern region of the state of São Paulo. The volunteers answered a questionnaire developed by the researchers for this purpose, with the Survey Monkey platform. Results and Discussion: In this study involved 99 men and 118 women with predominant age range of responses 20 - 29 years, equivalent to 70% of all responses. It was observed that 11% of the sample could not answer the definition of cancer but in contrast, 90.3% acknowledge a sedentary lifestyle and eating habits as risk factors. Only 22.6% recognized obesity as a risk factor for developing cancer, and a smaller percentage yet (13.4%) knew the correct concept of what being physically active according to the WHO. Verified the existence of the need for inclusion of subjects / activities on the subject in the curriculum of the course in Physical Education with a view to increasing the participation of these professionals in multidisciplinary teams working in health promotion.